Decreased mortality, laparotomy, and embolization rates for liver injuries during a 13-year period in a major Scandinavian trauma center - Gaski, Iver Anders (Trauma Surg Acute Care Open, 2018)
BACKGROUND: Although non-operative management (NOM) has become the treatment of choice in hemodynamically normal patients with liver injuries, the optimal management of Organ Injury Scale (OIS) grades 4 and 5 injuries is still controversial. Oslo University Hospital Ulleval (OUHU) has since 2008 performed angiography only with signs of bleeding. Simultaneously, damage control resuscitation was implemented. Would these changes result in a decreased laparotomy rate and need for angioembolization (AE), as well as decreased mortality? METHODS: We performed a retrospective study on all adult patients with liver injuries admitted at OUHU between 2002 and 2014. The total study population and patients with OIS grades 4 and 5 liver injuries underwent comparison between the periods before (P1) and after (P2) August 1, 2008. RESULTS: 583 patients were included (P1: 237, P2: 346), with a median Injury Severity Score (ISS) of 29. The total population and the subgroup of OIS 4 and 5 injuries were comparable in age, gender, mechanism of injury, injury severity and physiology. Overall laparotomy rates decreased from P1 to P2 (35%–24%; p<0.01), as did the AE rate (11%–5%; p<0.01). The 30-day crude mortality decreased from 14% to 7% (p<0.05). A logistic regression model predicted an OR of 0.45 (95% CI 0.21 to 0.98) for dying when admitted in P2. In OIS grades 4 and 5 injuries (n=149, median ISS 34), similar reduction in AE rate was seen (30%–12%; p<0.05). The NOM rate for OIS grades 4 and 5 injuries was 70%, with 98% success rate. For the 30% requiring surgery, the mortality remained high (P1 52%; P2 40%), despite more balanced transfusion strategy. DISCUSSION: Changes in resuscitation and treatment protocols were associated with decreased laparotomy, and AE rates as well as overall mortality. NOM is safe in 70% of patients with OIS grades 4 and 5 injuries, in contrast to the critically ill 30% requiring surgery who still have poor outcome. LEVEL OF EVIDENCE: IV.